2005
DOI: 10.1093/humrep/deh640
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden mutation in relation to fecundity and miscarriage in women with venous thrombosis

Abstract: Factor V Leiden mutation may support embryo implantation, as factor V Leiden carriers had fewer miscarriages in the first trimester with a similar overall miscarriage rate. Miscarriage of embryos with poor viability may be postponed until the second trimester in factor V Leiden carriers. Fecundity was not influenced by factor V Leiden status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
0
12
2
1
Order By: Relevance
“…Robertson et al [48] have called for larger epidemiological studies to justify the inclusion of routine screening for inherited thrombophilias in RSM clinics because of some conflicting reports [45,95] on the impact of inherited thrombophilia on RSM and other adverse pregnancy outcomes.…”
Section: Rsm Investigationsmentioning
confidence: 99%
“…Robertson et al [48] have called for larger epidemiological studies to justify the inclusion of routine screening for inherited thrombophilias in RSM clinics because of some conflicting reports [45,95] on the impact of inherited thrombophilia on RSM and other adverse pregnancy outcomes.…”
Section: Rsm Investigationsmentioning
confidence: 99%
“…The relationship between pregnancy loss and thrombophilia is a much-debated topic with well entrenched expert opinion on both sides and many studies reporting significant associations with pregnancy loss (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and others no associations (13)(14)(15)(16)(17). The thrombophilic factor V Leiden (FVL) G1691A mutation has been found to be significantly associated with recurrent pregnancy loss (RPL, R3 consecutive pregnancy losses <20 weeks gestation) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…However, it is possible that by selecting only women without any previous thromboembolism, Dizon-Townson et al (16) truncated the cohort to FVL-carrying women who were less likely to have subsequent uterine spiral artery thrombosis during pregnancy. Van Dunne et al (17) recruited consecutive patients who had sustained a first venous thrombosis event and compared the first 115 female patients with FVL versus 230 age-matched female patients without FVL. They reported that FVL carriers had no difference in pregnancy loss rate; specifically, first-trimester pregnancy loss rate was lower in FVL carriers than in noncarriers.…”
mentioning
confidence: 99%
“…Some studies reported a decreased risk of miscarriage in women with inherited thrombophilia [57,58], whereas one study reported that multiple genetic thrombophilic mutations in either partner seem to increase the risk of miscarriage in a subsequent pregnancy [59]. Larger epidemiological studies are clearly needed to justify testing couples with RM for inherited thrombophilia in routine clinical practice [60].…”
Section: Thrombophiliamentioning
confidence: 99%